2022
DOI: 10.1186/s13054-022-03892-7
|View full text |Cite|
|
Sign up to set email alerts
|

Association between hospital and ICU structural factors and patient outcomes in China: a secondary analysis of the National Clinical Improvement System Data in 2019

Abstract: Background Hospital and ICU structural factors are key factors affecting the quality of care as well as ICU patient outcomes. However, the data from China are scarce. This study was designed to investigate how differences in patient outcomes are associated with differences in hospital and ICU structure variables in China throughout 2019. Methods This was a multicenter observational study. Data from a total of 2820 hospitals were collected using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
7
1
1
Order By: Relevance
“…Traditionally, Adequate human resource allocation is one of the core element needed to ensure the quality of medical care[18], as ICU patients are highly dependent on nursing care, a shortage of nursing staff could be associated with insu cient supervision and recognition of state changes of the patients. Saker et al's study found that a high nurse-to-patient ratio was independently associated with a reduced risk of in hospital mortality [19], and Li et al found the similar result [13]. In our study, high nurse-to-bed ratio was also associated with lower VAP morbidity, but other factors such as patient-to-nurse ratio, physician-to-bed ratio showed the different trend.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Traditionally, Adequate human resource allocation is one of the core element needed to ensure the quality of medical care[18], as ICU patients are highly dependent on nursing care, a shortage of nursing staff could be associated with insu cient supervision and recognition of state changes of the patients. Saker et al's study found that a high nurse-to-patient ratio was independently associated with a reduced risk of in hospital mortality [19], and Li et al found the similar result [13]. In our study, high nurse-to-bed ratio was also associated with lower VAP morbidity, but other factors such as patient-to-nurse ratio, physician-to-bed ratio showed the different trend.…”
Section: Discussionsupporting
confidence: 69%
“…shown effective reducing VAP rates in multidisciplinary ICUs [12].An analysis of the National Clinical Improvement System Data in China highlighted the association between speci c ICU structural factors and patients' outcomes [13]. Therefore, the aim of this study was to investigate the ICU QI factors and the mortality and morbidity of VAP and identify the association between these variables and patient outcomes.…”
Section: Et Al Reported That Multifaceted Bundle Interventionsmentioning
confidence: 99%
“…En cuanto al tiempo de inicio de la hemodiálisis no existe diferencia entre ambos grupos debido a que en ambos grupos la distribución del tiempo de inicio de la hemodiálisis fue similar, a diferencia de (29,48) otros estudios donde demostraron asociación entre infección y hemodiálisis menor a 1 año , mientras que en otros estudios la infección fue mayor en el grupo con mayor tiempo de En relación a la ubicación del catéter de hemodiálisis, los sujetos con catéter femoral tuvieron mayor riesgo de infección en comparación con la ubicación yugular. Este hallazgo es similar a otros (14,51) estudios que comparan la ubicación el catéter y el riesgo de bacteriemia .…”
Section: Discussionunclassified
“…Following publication of the original article [ 1 ], the authors identified an error in the corresponding authors. The author Zhen Li is first author not a corresponding author.…”
Section: Correction To: Critical Care (2022) 26:24 101186/s13054-022-...mentioning
confidence: 99%